Kindergarten in Ontario – An Exceptional Case of a Publicly Funded Early Childhood Education Since 1883 - Wloka, Danuta (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2020)
Ontario has the distinction of having the longest and the richest history of public kindergarten in Canada. Ontario’s kindergarten is an exception in the field of publicly funded early childhood care and education in Canada, where the care and education of preschool-aged children has not been recognized as the government’s responsibility. This article traces the development of Ontario’s public kindergarten from its inception in 1883 to the current Full-Day Early Learning–Kindergarten Program. It identifies the evolving characteristics of kindergarten, trends, and paradigmatic changes in the analyzed period by using a longue durée approach as per Fernand Braudel. It explores the context of each historical phase of Ontario’s kindergarten development, the intersection of political agendas, ideologies, and economic and pragmatic considerations that were impacting kindergarten policies.